dz2 Band Links Frontier Orbitals and Charge Carrier Dynamics of Single-Atom Cocatalyst-Aided Photocatalytic H2 Production - Fu, Yiwei; Lu, Kejian; Hu, Anlan; Huang, Jie; Guo, Liejin; Zhou, Jian; Zhao, Jin; Prezhdo, Oleg V; Liu, Maochang (Journal of the American Chemical Society, 2023)
The Cu single-atom catalyst (SAC) supported on TiO2 exhibits outstanding efficacy in photocatalytic hydrogen evolution. The precise operational mechanism remains a subject of ongoing debate. The focus resides with the interplay linking heightened catalytic activity, dynamic valence state alterations of Cu atoms, and their hybridization with H2O orbitals, manifested in catalyst color changes. Taking anatase TiO2 (101) as a prototypical surface, we perform ab initio quantum dynamics simulation to reveal that the high activity of the Cu-SAC is due to the quasi-planar coordination structure of the Cu atom after H2O adsorption, allowing it to trap photoexcited hot electrons and inject them into the hybridized orbital between Cu and H2O. The observed alterations in the valence state and the coloration can be attributed to the H atom released during H2O dissociation and adsorbed onto the lattice O atom neighboring the Cu-SAC. Notably, this adsorption of H atoms puts the Cu-SAC into an inert state, as opposed to an activating effect reported previously. Our work clarifies the relationship between the high photocatalytic activity and the local dynamic atomic coordination structure, providing atomistic insights into the structural changes occurring during photocatalytic reactions on SACs.The Cu single-atom catalyst (SAC) supported on TiO2 exhibits outstanding efficacy in photocatalytic hydrogen evolution. The precise operational mechanism remains a subject of ongoing debate. The focus resides with the interplay linking heightened catalytic activity, dynamic valence state alterations of Cu atoms, and their hybridization with H2O orbitals, manifested in catalyst color changes. Taking anatase TiO2 (101) as a prototypical surface, we perform ab initio quantum dynamics simulation to reveal that the high activity of the Cu-SAC is due to the quasi-planar coordination structure of the Cu atom after H2O adsorption, allowing it to trap photoexcited hot electrons and inject them into the hybridized orbital between Cu and H2O. The observed alterations in the valence state and the coloration can be attributed to the H atom released during H2O dissociation and adsorbed onto the lattice O atom neighboring the Cu-SAC. Notably, this adsorption of H atoms puts the Cu-SAC into an inert state, as opposed to an activating effect reported previously. Our work clarifies the relationship between the high photocatalytic activity and the local dynamic atomic coordination structure, providing atomistic insights into the structural changes occurring during photocatalytic reactions on SACs.